Pengaruh Penerapan Model Pembelajaran Penemuan (Discovery Learning) Berbantuan Handout Terhadap Kemampuan Berpikir Kreatif dan Hasil Belajar Kimia Siswa - Saputri, Ika Kurnia Rara; Muntari, Muntari (Chemistry Education Practice, 2024)
This research aimed to investigate the effecf of discovery learning model assisted by handout to creative thinking ability and chemistry learningoutcomes of X class science students of SMAN 4 Mataram. This research used quasi-experimental research design with pre-test and post-test Control Group Design. The population in research include all of X grade students of IPA SMA Negeri 4 Mataram, were 143 people that distributed into 4 classes IPA. Sampling technique used was purposive sampling. The samples in this research was X IPA 1 as an experimental class and X IPA 2 as a control class. In experiment class was given treatment using the discovery learning model assisted by handout, on control class was given using conventional learning model. The instrument used was a descriptions test. Hypothesis tested in this study uses t-test on the analysis of creative thinking ability with statistical test results at a significant level of 5% indicated tcount (4,850) > ttable (1,669) which means that H0 is rejected and Ha is accepted and Mann Whitney U-test on the results analysis chemistry learning with statistical test results at a significant level of 5% shows Zcount (4.13) > Ztable (1,645) which means that H0 is rejected and Ha is accepted. Based on the results of the statistical tests of the two sample classes, it was found that the learning of discovery learning models assisted by handout had a positive influence on the ability to think creatively and the results of chemistry learning in class X science students of SMA Negeri 4 Mataram. Based on the results of observations of student learning activities discovery learning models assisted by handouts have a positive impact in increasing student activity during the chemistry learning process in class X science students of SMA Negeri 4 Mataram.